Antioxidant activity of peptides isolated from alfalfa leaf protein hydrolysate - Xie, Zhengjun; Huang, Junrong; Xu, Xueming; Jin, Zhengyu (Food chemistry, 2008)
Alfalfa leaf protein, a potential source of high quality protein for human consumption, was hydrolyzed with protease. Alfalfa leaf protein hydrolysate was fractionated by ultrafiltration and the obtained peptides were purified by dynamical adsorption. The antioxidant activity of alfalfa leaf peptides (ALPs) was investigated and compared with that of a native antioxidant, reduced glutathione (GSH), which was used as a reference. The reducing power of ALPs was 0.69 at 2.00mg/mL. ALPs at 1.60mg/mL and 0.90mg/mL exhibited 79.71% and 67.00% of scavenging activities on 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical and superoxide radical, respectively. In addition, ALPs showed 65.15% chelating effect on ferrous ion at 0.50mg/mL. The molecular weight of the peptides was determined and 67.86% of the total amount was below 1000Da. Combined with the result of the amino acid profiles, ALPs was believed to have high nutritive value in addition to antioxidant activity.